2019
DOI: 10.1200/jco.18.01314
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular High-Grade B-Cell Lymphoma: Defining a Poor-Risk Group That Requires Different Approaches to Therapy

Abstract: Purpose Biologic heterogeneity is a feature of diffuse large B-cell lymphoma (DLBCL), and the existence of a subgroup with poor prognosis and phenotypic proximity to Burkitt lymphoma is well known. Conventional cytogenetics identifies some patients with rearrangements of MYC and BCL2 and/or BCL6 (double-hit lymphomas) who are increasingly treated with more intensive chemotherapy, but a more biologically coherent and clinically useful definition of this group is required. Patients and Methods We defined a molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
311
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(331 citation statements)
references
References 32 publications
18
311
1
1
Order By: Relevance
“…The adverse prognostic effect of MYC translocation seems to increase in the presence of an additional chromosomal breakpoint involving the BCL2 or BCL6 loci. These 'double-hit' lymphomas seem to have an extremely aggressive clinical course and poor response to standard chemotherapy (Sha et al, 2019). Besides, gene expression profiling for the cell of origin is a genomics tool that utilizes DNA microarray to assess gene expression and at least three molecularly distinct forms of DLBCL have been identified: the germinal centre Bcell, activated B-cell and primary mediastinal B-cell subtypes (Alizadeh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The adverse prognostic effect of MYC translocation seems to increase in the presence of an additional chromosomal breakpoint involving the BCL2 or BCL6 loci. These 'double-hit' lymphomas seem to have an extremely aggressive clinical course and poor response to standard chemotherapy (Sha et al, 2019). Besides, gene expression profiling for the cell of origin is a genomics tool that utilizes DNA microarray to assess gene expression and at least three molecularly distinct forms of DLBCL have been identified: the germinal centre Bcell, activated B-cell and primary mediastinal B-cell subtypes (Alizadeh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Through the use of gene expression profiling, recognition of high‐risk disease has recently moved beyond FISH identification of the three described translocations. Two groups used independent data sets to look either for a Burkitt‐like gene expression signature or a signature associated with the known presence of DHL in large cohorts of patients with DLBCL. This approach identified most DHL patients but also many non–double‐hit lymphomas, representing over half of the group, cosegregated with the same gene expression signatures.…”
Section: Novel Approachesmentioning
confidence: 99%
“…Favorable outcomes of DH-FL were also observed in other studies in patients treated with conventional or intensive schemes [25][26][27]. Recent studies have defined the molecular high-grade B-cell lymphoma profile (MGH) by gene expression and mutational analysis [28,29]. These studies identified cases that did not carry MYC rearrangements and behaved aggressively.…”
Section: Discussionmentioning
confidence: 73%